1995
DOI: 10.1002/ajim.4700270112
|View full text |Cite
|
Sign up to set email alerts
|

Occupational associations with lung cancer in two Ontario cities

Abstract: A death certificate based case-control study of lung cancer in two Ontario cities was performed to estimate the risk of lung cancer attributable to occupation in Ontario, and to estimate the proportion of occupational lung cancers receiving compensation from the Workers' Compensation Board. Occupation and industry were identified from the death certificate. A priori occupations for analysis were those whose members had received compensation for occupational cancer from the Ontario Workers' Compensation Board. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
(6 reference statements)
2
7
0
Order By: Relevance
“…Joint exposure to smoking habit and certain occupations can raise the risk of lung cancer by over 200-fold. Our findings are in line with earlier studies that have reported a link between a series of occupations-whether individually [Robinson et al, 1995[Robinson et al, , 1996Steenland and Palu, 1999] or as groups- [Finkelstein, 1995;Stellman et al, 1998] and higher risk of lung cancer. Also pointing in this same direction are the studies undertaken by Soll-Johanning et al [1998] and Stellman et al [1998], in which a slight rise in risk was detected with longer exposure as professional drivers in the former case, and to wood dust in the latter.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Joint exposure to smoking habit and certain occupations can raise the risk of lung cancer by over 200-fold. Our findings are in line with earlier studies that have reported a link between a series of occupations-whether individually [Robinson et al, 1995[Robinson et al, , 1996Steenland and Palu, 1999] or as groups- [Finkelstein, 1995;Stellman et al, 1998] and higher risk of lung cancer. Also pointing in this same direction are the studies undertaken by Soll-Johanning et al [1998] and Stellman et al [1998], in which a slight rise in risk was detected with longer exposure as professional drivers in the former case, and to wood dust in the latter.…”
Section: Discussionsupporting
confidence: 95%
“…On the basis of this classification, risk professions can be divided into two groups, the first group being made up of professions that involve inhalation of solid particulates, [Roscoe et al, 1989;Finkelstein, 1995;Qing-Sheng et al, 1995;Robinson et al, 1995;Stern et al, 1995;Firth et al, 1996; Robinson et al, 1996;Rousteenoja et al, 1996;Wang et al, 1996;Lubin and Boice, 1997; Andersen et al, 1999;González and Agudo, 1999;Pezzotto and Poletto, 1999] and the second of professions that involve exposure to organic chemical compounds [Guberan et al, 1992;Armstrong et al, 1994;Sorahan et al, 1994;Finkelstein, 1995;Qing-Sheng et al, 1995;De Stefani et al, 1996;Firth et al, 1996;Leigh, 1996;Jakobsson et al, 1997;Lynge et al, 1997;Ward et al, 1997;Grimsrud et al, 1998;Soll-Johanning et al, 1998; Andersen et al, 1999;Pezzotto and Poletto, 1999;Steenland and Palu, 1999] or radiation [Ritz, 1999].…”
mentioning
confidence: 99%
“…Diesel emissions containing a variety of polycyclic aromatic hydrocarbons could be the etiologically relevant exposures for lung cancer in this industry. Evidence from the literature that links excess risk of lung cancer among transport workers to diesel emissions supports our notion Finkelstein 1995;Jarvholm and Silverman 2003;Jockel et al 1998;Siemiatycki et al 2004). The IARC identified diesel engine exhaust as probable human carcinogen (IARC 1989a).…”
Section: Transportationsupporting
confidence: 74%
“…Due to inadequate smoking information, the vast majority of the epidemiology studies evaluating lung cancer risk in welders were not able to sufficiently control for smoking (Hansen, Lauritsen, and Skytthe 1996;Steenland, Beaumont, and Elliot 1991;Danielsen, Langard, and Andersen 1996;Moulin et al 1993;Andersen 1998, 2000;Hull et al 1989;Simonato et al 1991;Steenland 2002;Tola et al 1988;Moulin 1997;Danielsen, Langard, and Andersen 1993;Newhouse, Oakes, and Woolley 1985;Weiss 1980, 1981;Becker, Chang-Claude, and Frentzel-Beyme 1991;Milham 1985;Milne et al 1983;Andersen et al 1999;Becker 1999;Fletcher and Ades 1984;Polednak 1981;Puntoni et al 2001;Melkild et al 1989;Menck and Henderson 1976;Ambroise, Wild, and Moulin 2006;Stern, Sweeney, and Ward 1997;de Silva et al 1999;Park, Krebs, and Mirer 1994;Finkelstein 1995;Milham 1997;Burnett, Maurer, and Dosemeci 1997;Firth et al 1993). This introduces a significant bias as it has been well documented that welders tend to smoke more than the general population (Dunn, Linden, and Breslow 1960;Hull et al 1989;Steenland 2002;Danielsen, Langard, and Andersen 1993;Hunnicut, Cracovaner, and Myles 1964;Office of Population and Censu...…”
Section: Failure To Control For Smokingmentioning
confidence: 98%